AB0878 THE COMPARISON EFFECTS OF INTRA-ARTICULAR INJECTION OF PLATELET RICH PLASMA (PRP), PLASMA RICH IN GROWTH FACTOR (PRGF), HYALURONIC ACID (HA), AND OZONE IN KNEE OSTEOARTHRITIS; A ONE YEAR RANDOMIZED CLINICAL TRIAL. (2nd June 2020) - Raeissadat, S. A.; Ghazi Hosseini, P.; Bahrami, M. H.; Salman Roghani, R.; Fathi, M.; Gharooee Ahangar, A.; Darvish, M.
Abstract : Background: Knee osteoarthritis (OA) as a common progressive degenerative condition is one of the most important leading causes of disability and relative dependence. Worldwide prevalence of symptomatic knee OA has estimated 3.8%. It affects more than 20% of over 45-year-old population. Among the minimally invasive methods recommended for knee OA management is intra-articular injections for which a large array of products have been used. Despite all the existing options, there is still no general consensus on the choice and priority of the best intra-articular injection in knee osteoarthritis. Objectives: Our study compare the short and long-term efficacy of the intra articular injections (IAIs) of hyaluronic acid (HA), platelet-rich plasma (PRP), plasma rich in growth factors (PRGF), and ozone in patients with knee osteoarthritis (OA). Methods: In this single-blinded randomized clinical trial, 238 patients with mild to moderate knee OA were randomized into4 groups of IAIs: HA (3 doses weekly), PRP (2 doses with 3 weeks interval), PRGF (2 doses with 3 weeks interval), and Ozone (3 doses weekly). Our outcome measures were the mean changes from baseline until 2, 6, and 12 months post intervention in scores of visual analog scale, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Lequesne index. Results: A total of 200 patients enrolled final analysis. The mean age of patients was 56.9 ± 6.3 years, and69.5% were women. In 2 months follow up, significant improvement of pain, stiffness, and function were seen in all groups compared to the baseline, but the ozone group had the best results(P<0.05). In 6 month follow up HA, PRP, and PRGF groups demonstrated better therapeutic effects in all scores in comparison with ozone (P<0.05).At the end of the 12th month, only PRGF and PRP groups had better results versus HA and ozone groups in all scores (P<0.05).Despite the fact that ozone showed better early results, its effects begin to wear off earlier than other products and ultimately disappear in 12 months. Conclusion: Ozone injection had rapid effects and better short-term results after 2 months, but its therapeutic effects did not persist after 6 months and at the 6-month follow up, PRP, PRGF and HA were superior to ozone. Only patients in PRP and PRGF groups improved symptoms persisted for 12 months. Therefore, these products could be the preferable choices for long-term management. References: [1]Wang-Saegusa A, Cugat R, Ares O, Seijas R, Cuscó X, Garcia-Balletbó M. Infiltration of plasma rich in growth factors for osteoarthritis of the knee short-term effects on function and quality of life. Archives of orthopaedic and trauma surgery. 2011;131(3):311-7. [2]De La Mata J. Platelet rich plasma.A new treatment tool for the rheumatologist?ReumatologíaClínica (English Edition). 2013;9(3):166-71. [3]Raeissadat SA, Rayegani SM, Sedighipour L, Bossaghzade Z, Abdollahzadeh MH, Nikray R, et al. The efficacy of electromyographic biofeedback on pain, function, and maximal thickness of vastus medialis oblique muscle in patients with knee osteoarthritis: a randomized clinical trial. Journal of pain research. 2018;11:2781. [4]Lawrence RC, Felson DT, Helmick CG, Arnold LM, Choi H, Deyo RA, et al. Estimates of the prevalence of arthritis and other rheumatic conditions in the United States: Part II. Arthritis & Rheumatism. 2008;58(1):26-35. [5]Tehrani-Banihashemi A, Davatchi F, Jamshidi AR, Faezi T, Paragomi P, Barghamdi M. Prevalence of osteoarthritis in rural areas of I ran: a WHO-ILAR COPCORD study. International journal of rheumatic diseases. 2014;17(4):384-8. [6]Rayegani SM, Raeissadat SA, Heidari S, Moradi-Joo M. Safety and effectiveness of low-level laser therapy in patients with knee osteoarthritis: a systematic review and meta-analysis. Journal of lasers in medical sciences. 2017;8(Suppl 1):S12. Disclosure of Interests: None declared